Effects of receptive-productive integration tasks and prior knowledge of component words on L2 collocation development. (June 2017) - Zhang, Xiaoyan
Abstract: This study examines the effects of a receptive-productive integration task on the development of collocation knowledge of form, form and meaning, and grammar in comparison with the effects of productive and receptive tasks. In addition, the study investigates how prior knowledge of component nouns in verb-noun collocations affects collocation learning. Four intact classes of Chinese English as a foreign language (EFL) sophomores were randomly assigned to a productive group, a receptive group, a receptive-productive integration group, and a control group. The 12 target verb-noun collocations fell into two categories, one containing a known noun and one containing an unknown noun. The study found that (1) in light of both immediate and long-term gains, the integration group performed better than both the receptive and productive groups and (2) participants produced significantly more correct responses for collocations without unknown words than for collocations with unknown words across two post-test sessions.